Factors Affecting Ankle Functional Scores at Spastic Diplegia Cerebral Palsy Patients that Have Been Performed Single Event Multi Level Surgery - Andryanto, Aryo Budiyogo; Satriadi, Anung Budi; Idulhaq, Mujaddid (Indonesian Journal of Medicine, 2019)
Background: Single Event Multi Level Surgery (SEMLS) is the treatment most often used to correct deformities and functional in children with Spastic Diplegic Cerebral Palsy. There is no research in Indonesia that assesses the ankle function in patients with Spastic CP Diplegic has done SEMLS. The purpose of this study was to determine the influence of age, gender and time period after surgery with functional ankle patients with CP Spastic Diplegic that has been done SEMLS in the RSO. Prof. Dr. R. Soeharso Surakarta (RSO).Subjects and Method: This study was a cross sectional study in 43 patients (25 male and 18 female) patients with Spastic Cerebral Palsy Diplegia that has been done SEMLS in pediatric orthopedics clinic RSO. Prof.dr.R.Soeharso Surakarta at least 3 months postoperatively, since January 1st 2013 to December 31st 2014. We assessed ankle function using the Oxford Ankle Foot Questionnaire for Children. From the results of the questionnaire we value outcomes as a percentage and we regrouped into 4 groups: value of 91% - 100% for excellent value, 81% - 90% for good, 71% - 80% for fair and if less than 70% for poor. Then we did impact assessment for age, sex and time of the postoperative with functional ankle score of patients with examination of linear regression model analysis.Results: There were 52 patients with Spastic CP Diplegi have done SEMLS but only 43 patients who qualified the inclusion criteria, the youngest patient was 5 years old and the oldest 15 years old with a mean age of 8.3 years. From the 43 patients, 25 are men and 18 were women. Postoperative time with the fastest time of observation was 5 months and the longest was 26 months with a mean of 14.3 months postoperatively SEMLS. From the 43 patients there are 11 patients (25%) function are excellent, 21 patients (49%) are good, 8 patients (19%) are fair, and 3 (7%) are poor. Age factor significantly influence the functional ankle score (p = 0.013) and postoperative time factors also significantly influence the functional score Ankle with (p = 0.04). While gender has no effect on the functional ankle score (p= 0.266).Conclusion: Paediatri Orthopaedic clinic at RSO. Prof. Dr. R. Soeharso has succed treated patients with CP Spastic Diplegic that have performed SEMLS. Age and time of postoperative significantly influence the functional ankle score in patients with CP Spatik Diplegic that have been done SEMLS. While the sex of the patients had no effect on the functional ankle score in patients with CP Spastic Diplegic that have been done SEMLS.Keywords: RSO Prof. Dr. R. Soeharso, CP Spastic Diplegic, SEMLS, Ankle Functional ScoreCorrespondence: Aryo Budiyogo Andryanto. Student of Orthopaedic and Traumatology school of Medicine, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java.Indonesian Journal of Medicine (2019), 4(3): 228-231https://doi.org/10.26911/theijmed.2019.04.03.05